Wages of Nurturant and Reproductive Care Workers: Individual and Job Characteristics, Occupational Closure, and Wage-Equalizing Institutions. (18th April 2018) - Budig, Michelle J; Hodges, Melissa J; England, Paula
Abstract: Despite the work's social importance, nurturant and reproductive care workers earn less than others with comparable human capital and work demands. We explore three broad questions related to pay for care work. First, we examine nurturant and reproductive care penalties together to investigate what mechanisms produce the lower wages for these workers. Second, we examine how occupational closure through education credentials and licensing requirements creates varying returns to care work. Finally, we explore the roles of wage equalizing institutions—labor unions and government sector care provision—in reducing wage disparities associated with care work. Using the 1979-2012 waves of the National Longitudinal Survey of Youth (NLSY) and fixed-effects regression models, we find that selection on stable factors and human capital differences explain much of the lower wages for reproductive workers, but none of the low wages of nurturant workers. However, compared to non-care workers, college-educated nurturant care workers receive lower returns to work experience, suggesting limitations in how much learning can increase efficiency in care work, given the labor intensive, face-to-face nature of much of it. Occupational closure matters: care jobs with the highest educational and licensing requirements pay a wage bonus, while less closed care occupations incur a penalty. Wage equalizing institutions have both floor and ceiling effects on care worker wages that mitigate care penalties for selected workers: women reproductive workers and women in low-education/high-licensing occupations. More consistently, ceiling effects of these institutions lower the wages of otherwise higher paid care workers: nurturant and high-education/high licensing occupations.